2014
DOI: 10.1152/ajpheart.00641.2013
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage-derived IL-18 and increased fibrinogen deposition are age-related inflammatory signatures of vascular remodeling

Abstract: Padron RI. Macrophage-derived IL-18 and increased fibrinogen deposition are age-related inflammatory signatures of vascular remodeling. Am J Physiol Heart Circ Physiol 306: H641-H653, 2014. First published January 10, 2014; doi:10.1152/ajpheart.00641.2013.-Aging has been associated with pathological vascular remodeling and increased neointimal hyperplasia. The understanding of how aging exacerbates this process is fundamental to prevent cardiovascular complications in the elderly. This study proposes a mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 51 publications
1
34
0
Order By: Relevance
“…(Lakatta & Levy, ; Meyer et al, ) Previous studies have showed that aging exacerbates neointima lesions after vascular injury through promoting macrophage infiltration and higher sensitivity of SMCs to proliferation stimuli. (Eghbalieh et al, ; Rodriguez‐Menocal et al, ) Aging induces superoxide production in the PVAT and contributes to arterial stiffness. Herein, our findings show that PVASC transcriptional landscape is unexpectedly diverse between young and aged mice.…”
Section: Discussionmentioning
confidence: 99%
“…(Lakatta & Levy, ; Meyer et al, ) Previous studies have showed that aging exacerbates neointima lesions after vascular injury through promoting macrophage infiltration and higher sensitivity of SMCs to proliferation stimuli. (Eghbalieh et al, ; Rodriguez‐Menocal et al, ) Aging induces superoxide production in the PVAT and contributes to arterial stiffness. Herein, our findings show that PVASC transcriptional landscape is unexpectedly diverse between young and aged mice.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence obtained suggested that inflammation was implicated in tissue remodeling. 16,17 Even though it was proposed bladder progressed from inflammation to fibrosis in BOO, few studies highlighted the important role of inflammation in the pathological process. 7 We confirmed the inflammatory response in BOO by screening inflammatory genes, which were extensively studied in smooth muscles.…”
Section: Discussionmentioning
confidence: 99%
“…If there is too much extracellular matrix there is an increase in cardiac stiffness and diastolic dysfunction in aged organisms (Ma et al 2013). Cardiac stiffness increased with age due to the increased amount of collagen content and fibrinogen deposit in old animals (Horn et al 2012; Rodriguez-Menocal et al 2014; Yabluchanskiy et al 2014). …”
Section: Quality Control Mechanisms In Cardiac Agingmentioning
confidence: 99%